2014
DOI: 10.15430/jcp.2014.19.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Carnosol: A Phenolic Diterpene With Cancer Chemopreventive Potential

Abstract: Cancer is an unbeaten health challenge for the humankind. After striving for decades to find a cancer cure, attention has now been shifted to reduce the morbidity and mortality from cancer by halting the course of tumor development. Numerous bioactive phytochemicals, especially those present in edible and non-edible plant species, have been reported to reduce the risk of many cancers. Multiple lines of evidence suggest that carnosol, a phenolic diterpene present in rosemary (Rosmarinus officinalis L.), holds t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 46 publications
1
26
0
1
Order By: Relevance
“…Rosemary is a rich source of beneficial phenolic compounds, carnosol, carnosic and rosmarinic acids, and related effective compounds having strong antioxidant, anti-cancer and antiinflammatory activities (Chun et al, 2014;Rocío-Teruel et al, 2015). Herbal additives may act by more than one mechanism, affecting feed intake and conversion, stimulating the secretion of digestive enzymes and gastrointestinal motility, as well as immune and endocrine functions in addition to their antioxidant, antimicrobial, antiviral, anti- …”
Section: Antioxidant Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Rosemary is a rich source of beneficial phenolic compounds, carnosol, carnosic and rosmarinic acids, and related effective compounds having strong antioxidant, anti-cancer and antiinflammatory activities (Chun et al, 2014;Rocío-Teruel et al, 2015). Herbal additives may act by more than one mechanism, affecting feed intake and conversion, stimulating the secretion of digestive enzymes and gastrointestinal motility, as well as immune and endocrine functions in addition to their antioxidant, antimicrobial, antiviral, anti- …”
Section: Antioxidant Indicesmentioning
confidence: 99%
“…Studies have described various biological impacts and protective effects of rosemary (Rosmarinus officinalis L.), including antioxidant, antibacterial, anti-inflammatory, anticancer, immunomodulatory and health-promoting activities (FlorouPaneri et al, 2006;Chun et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Rosemary-leaf extracts ( Rosmarinus officinalis L.) have received special attention since European Food Safety Authority and U.S. Food and Drug Administration approved their use as food additive, demonstrating to be safe for human health at specific compositions [27,28]. Several rosemary compounds, principally carnosol (CS) [29,30,31,32], carnosic acid (CA) [33,34,35], and ursolic acid [36,37,38], have demonstrated different anticancer activities, such as anti-proliferative, antiinvasive, and antitumorigenic effects, in a dose-dependent manner. Interestingly, although several of the observed anti-proliferative effects of rosemary extracts have been commonly attributed to some of these components, in many cases the effect of the complete extract is higher than that exerted by the individual compounds [20,21,30,33,39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Rosemary is rich in carnosol and carnosic acid, and is used for a variety of purposes [17], including in foods [38]. By evaluating anti-melanogenic activity, we found that the ethanol extract of C. longissima leaf was also rich in these substances and strongly inhibited MITF gene expression.…”
Section: Discussionmentioning
confidence: 84%